Differential Roles of Mitochondrial Translocation of Active Caspase-3 and HMGB1 in Neuronal Death Induced by Status Epilepticus - Kim, Ji-Eun; Kang, Tae-Cheon (Frontiers in Cellular Neuroscience, 2018)
Under pathophysiological conditions, aberrant mitochondrial dynamics lead to the different types of neuronal death: excessive mitochondrial fission provokes apoptosis and abnormal mitochondrial elongation induces necrosis. However, the underlying mechanisms how the different mitochondrial dynamics result in the distinct neuronal death patterns have been elusive. In the present study, status epilepticus (SE) evoked excessive mitochondrial fission in parvalbumin (PV) cells (one of GABAergic interneurons) and abnormal mitochondrial elongation in CA1 neurons in the rat hippocampus. These impaired mitochondrial dynamics were accompanied by mitochondrial translocations of active caspase-3 and HMGB1 in PV cells and CA1 neurons, respectively. WY14643 (an activator of mitochondrial fission) aggravated SE-induced PV cell loss by enhancing active caspase-3 induction and its mitochondrial translocation, which were attenuated by Mdivi-1 (an inhibitor of mitochondrial fission). Mitochondrial HMGB1 import was not observed in PV cell. In contrast to PV cells, Mdivi-1 deteriorated SE-induced CA1 neuronal death concomitant with mitochondrial HMGB1 translocation, which was abrogated by WY14643. These findings suggest that SE-induced aberrant mitochondrial dynamics may be involved in translocation of active caspase-3 and HMGB1 into mitochondria, which regulate neuronal apoptosis and necrosis, respectively.